2019
DOI: 10.3892/ol.2019.10975
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib suppresses lipopolysaccharide‑stimulated oral squamous cell carcinoma proliferation in�vitro and in�vivo

Abstract: Periodontitis is one of the most common chronic oral inflammatory conditions worldwide and is associated with a risk of developing oral squamous cell carcinoma (OSCC). Porphyromonas gingivalis is a major pathogen in periodontitis, and its lipopolysaccharide (LPS) promotes the expression of cyclooxygenase-2 (COX-2) in OSCC both in vivo and in vitro. Celecoxib is a selective COX-2 inhibitor; however, its antitumor effects on P. gingivalis LPS-stimulated OSCC and the underlying molecular mechanism remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Likewise, Yoshida et al. 20 noted that 5.1% of patients treated with proton beam radiotherapy for hepatocellular carcinoma developed an alpha-fetoprotein spike at a median of 1 month.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, Yoshida et al. 20 noted that 5.1% of patients treated with proton beam radiotherapy for hepatocellular carcinoma developed an alpha-fetoprotein spike at a median of 1 month.…”
Section: Discussionmentioning
confidence: 96%
“…[ 51 52 ] In the study of squamous cell carcinoma of head and neck, it was found that lipopolysaccharide in Porphyromonas gingivalis (the main pathogen of periodontitis) promotes the expression of COX-2 in oral squamous cell carcinoma, while celecoxib can significantly inhibit the development of tumor, and inhibit the transformation of G0/G1-S phase and reduce the proliferation of tumor cells by increasing the expression of p21. [ 53 54 ] Furthermore, celecoxib can promote T cells to play a role in the tumor microenvironment through the COX-2 pathway. Since 2,3-dioxygenase (IDO) can decompose L-tryptophan into L-kynurenine, a large amount of IDO decomposition of tryptophan in the tumor microenvironment will cause immune T lymphocytes to not effectively recognize tumor cells, and even accelerate T lymphocyte apoptosis.…”
Section: Celecoxib Inhibits Tumors Through Cox-2/pge 2 mentioning
confidence: 99%
“…Numerous studies have reported the chemopreventive efficacy of celecoxib in several precancerous lesions and cancer types, including colon polyp, colorectal adenomas, lung cancer, and prostate cancer [ 13 , 14 , 15 , 16 , 17 ]. Furthermore, celecoxib was found to prevent tumor growth through multiple pathways and targets [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In terms of the molecular mechanism of celecoxib, it can regulate FAK, Cx43, p21, and Ki-67 molecules, and block AKT activation [ 20 , 22 , 24 ], which can inhibit tumor cell proliferation and induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, celecoxib was found to prevent tumor growth through multiple pathways and targets [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In terms of the molecular mechanism of celecoxib, it can regulate FAK, Cx43, p21, and Ki-67 molecules, and block AKT activation [ 20 , 22 , 24 ], which can inhibit tumor cell proliferation and induce apoptosis. Moreover, celecoxib is involved in ERK1/2 MAPK and PI3K/AKT pathways, exerting an antiangiogenic effect [ 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%